Short movies, wrong move: defense of an errant narrativity in Gonçalo M. Tavares and Wim Wenders - Klumb, Frederico (2022)
This work sought to establish a comparative reading between the book Short movies, by Portuguese writer Gonçalo M. Tavares, and the film Wrong move, by german filmmaker Wim Wenders. Taking as a starting point the propositions of an expansive comparativeism coined by Florencia Garramuño, among others, we tried to illuminate the narrativity in both works, discussing, also, the ideas of autonomy, hybridity and artistic fields.